Pengembangan Buku Ajar Simulasi dan Pemodelan Fisika dengan Unity3D Berbasis Self Regulated Learning - Fachrizal Rian Pratama; Anjar Hero Sasmiko (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
This study aims to develop a simulation and modeling physics textbook assisted by Unity3D software with a self-regulated learning approach. This research uses Development and Research method through 4D Model. The definition stage is carried out by determining the characteristics of the textbook that will be developed through the initial study. The design stage is done by choosing the format and design of the textbook to produce the first correction (draft). The development stage is carried out to have the second draft, third correction, and the final product of the textbook. The second correction is obtained through the revised expert validation results that have been recommended. The third correction is the acquisition of small group test results by taking them randomly. Based on the results of field tests on students who are taking Physics Simulation and Modeling courses, the final product of the textbook is obtained. One of the textbook features and tools developed is the project assignment feature and the video tutorial tool. Based on the validation of the textbook and its supporting devices, the criteria are very feasible and ready to be used and can guide student learning independently through the features in the textbook. The development of this textbook is expected to assist in developing simulations and modeling in physics and other fields of science, such as engineering and health.